Arthur Loomis Sanborn, Annotated Statutes of Wisconsin, Containing the General Laws in Force October 1, 1889, Also the Revisers' Notes to the Revised Statutes of 1858 and 1878, Notes of Cases Construing and Applying the Constitution and Statutes, and the Rules of the County and Circuit Courts and of the Supreme Court, at 2226, § 4397 (Vol. 2, 1889) - (:unkn) unknown (My University, 1889)
Any person who shall go armed with any concealed and dangerous weapon, shall be punished by imprisonment in the county jail not more than six months, or by fine not exceeding one hundred dollars: provided, this section shall not apply to any policeman or officer authorized to serve process.
Keywords: CARRY - CONCEALED